Prevention of bullying in schools: an ecological model - Carvalhosa, S. F. (INFAD Revista de Psicología/International Journal of Developmental and Educational Psychology, 2009)
The main goal is to understand the different processes, characteristics, settings and timing of bullying behaviour according to ecological system theory. The data is based on the Health Behaviour in School-aged Children surveys conducted in 1997/1998 and 2001/2002 in which students with average ages of 11.5, 13.5 and 15.5 years participated. The data were analysed using descriptive statistics, logistic regression, and structural equation modelling and multiple regression. Victims are usually highly associated with internalizing behaviours, bullies frequently indicate a high association with externalizing behaviours, and bully/victims often have strong associations with excessive and extreme behaviours of both an internalizing and an externalizing type. For each country, with in the school, victims and bully/victims reported lower levels of support from classmates, and bullies and bully/victims received similar support from teachers. Outside school, victims reported lower levels of support from friends. Across nations, bullying attained its highest prevalence, for both victims and bullies, in the lower and higher GDP countries (U-shaped curve). These findings support the assumption that involvement in bullying will damage the healthy development of young people and turn the world into malfunctioning societies. It is important for society to develop strategies that might prevent bullying, and school is considered to be a particularly important setting for implementing systematic approaches towards preventing bullying behaviour. Furthermore, school is in a position to initiate collaboration with both parents and local community which is important for wide reaching impact of the prevention strategies.